Redefining conservation through collective memory - Khusnul Hanifati; Yulia Nurliani Lukito (Department of Architecture Universitas Muhammadiyah Jakarta, 2020)
Conservation theory is determined by the concept of memory. Collective memory is an accumulation of events remembered by a group who shared and involved in shaping the memory. It plays an important role to articulate meaning that relevant to the current context, needs, and agenda. In old quarter of Jakarta, the concept of memory was produced as a collective effort to reconstruct Kampung Kunir which had been evicted in 2015. With its strategic location, it is impossible to exclude the revitalization of Kota Tua to its enclave surrounding. The community surrounding Kota Tua experiencing a conflict of inclusion when the revitalization process begun. Kota Tua has become tourism object while, in reality, it is surrounded by kampungs, creating a distance between the local residents and Kota Tua. After the eviction of Kampung Kunir, the government create a program to reconstruct the settlement for several families who resist to live there. A group of architect, ASF-Indonesia, was involve in facilitating physical and historical mapping, and projecting the new Kampung Kunir. Thus the reconstruction of Kampung Kunir can be seen as an effort from the community to redefine conservation and question for whom the conservation is. This paper seeks to elucidate how collective memory plays as an important aspect to conserve historical sites.